2008
DOI: 10.1080/10428190701713630
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of T-cell lymphoma associated with hemophagocytic syndrome: Comparison of T-cell lymphoma with and without hemophagocytic syndrome

Abstract: T-cell lymphoma-associated hemophagocytic syndrome (T-LAHS) has been frequently reported in Asian countries and is considered with extremely poor prognosis. To summarize its clinical characteristics and explore its early diagnosis and treatment, we retrospectively analyzed the records of 113 patients with aggressive T cell lymphoma, of which 28 were associated with LAHS. According to WHO classification (2001), 22 cases were classified into peripheral T-cell lymphoma (unspecified), 2 into extranodal NK/T-cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 21 publications
1
58
0
1
Order By: Relevance
“…There have been previous reports about prognostic factors for PTCL-NOS, including the presence of EBV (9), the expression of cytotoxic molecules such as granzyme B and TIA-1 (10), and hemophagocytic syndrome complications (11). The present patient demonstrated some adverse prognostic factors, including EBV positivity, cytotoxic molecule expression, and multiple drug resistance.…”
Section: Discussionmentioning
confidence: 54%
“…There have been previous reports about prognostic factors for PTCL-NOS, including the presence of EBV (9), the expression of cytotoxic molecules such as granzyme B and TIA-1 (10), and hemophagocytic syndrome complications (11). The present patient demonstrated some adverse prognostic factors, including EBV positivity, cytotoxic molecule expression, and multiple drug resistance.…”
Section: Discussionmentioning
confidence: 54%
“…In Japan, the annual incidence of HLH was estimated as 1 in 800,000 per year (primarily the acquired form) [3]. HLH was the most common in NK/ T cell lymphoma (i.e., up to 24.7 %) [10]. The mechanism of triggering HLH in lymphoma has not been fully elucidated, but a mutation of the perforin gene is partly responsible [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of HLH secondary to lymphoma is unfavorable, and the median survival time is less than 40 days [2,10]. Importantly, survival has been shown to be dependent on the type of lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…A study of T-cell lymphoma-associated HLH revealed elevated lactate dehydrogenase, ferritin, triglycerides and hypofibrinogenemia in the group with HLH as compared to those without HLH. This study showed a significantly worse outcome in T-cell lymphoma with HLH (median survival 40 days vs 8 months in group without HLH) [4].…”
Section: Dear Editormentioning
confidence: 95%
“…The clinical features and diagnostic criteria of acquired HLH are similar to the familial form, except for the family history. Of the lymphomas, T-cell lymphoma and Hodgkin lymphomas have been reported frequently with HLH [3,4]. T-cell lymphoma-associated HLH usually involves extra-nodal sites like nasal, cutaneous or hepatosplenic locations.…”
Section: Dear Editormentioning
confidence: 99%